2000
DOI: 10.20965/jrm.2000.p0165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Swimming Properties and Design of Spiral-Type Magnetic Micromachine

Abstract: The swimming properties of spiral-type magnetic micromachines were analyzed theoretically by 2-dimensional finite volume. Good agreement between experimental and theoretical results was obtained. Swimming properties of micromachines depend strongly on the operational environment, including the flow field and machine structure. We analyzed the effect of machine shape on swimming properties. The optimum design of the blade shape was obtained by simulation. Based on optimum design, the micromachine was fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Thus, to develop a swimming micromachine for medical applications, the device must be capable of functioning under a very wide range of values. In our previous studies we proposed a spiral-type magnetic micro-machine and analyzed fluid motion to obtain the optimum shape of this machine for operation within fluids with kinematic viscosities ranging from 5 mm /s to 100 mm /s [4]- [7]. In our experiments, we demonstrated that the micro-machine could swim upstream against a fluid flowing with a velocity higher than that of venous blood [5].…”
Section: Swimming Of Magnetic Micro-machines Under a Very Wide-range mentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, to develop a swimming micromachine for medical applications, the device must be capable of functioning under a very wide range of values. In our previous studies we proposed a spiral-type magnetic micro-machine and analyzed fluid motion to obtain the optimum shape of this machine for operation within fluids with kinematic viscosities ranging from 5 mm /s to 100 mm /s [4]- [7]. In our experiments, we demonstrated that the micro-machine could swim upstream against a fluid flowing with a velocity higher than that of venous blood [5].…”
Section: Swimming Of Magnetic Micro-machines Under a Very Wide-range mentioning
confidence: 90%
“…The magnetic torque was calculated by multiplying the product of the magnetic moment on the machine and the intensity of the magnetic field in the experiments of Figs. 2 and 3 (A-type, 2.9 Nm; B-type, 66 Nm), and the load torque was calculated by analyzing the flow field around the machine and the forces acting on the machine [7]. The calculated results are shown in Fig.…”
Section: B Step-out Frequencymentioning
confidence: 99%
“…In Fig. 2, the plots show the experimental results, and the solid line shows the analysis result [4]. The arrow in this graph was the step-out frequency at kinematic viscosity of 100 mm 2 /s.…”
Section: Swimming Velocitymentioning
confidence: 98%
“…3 shows the relation between the kinematic viscosity and the torque. The plots show the experimental results of the magnetic torque and the solid line shows the analysis result of load torque [4]. The torque increased with the increase in the kinematic viscosity.…”
Section: Load Torquementioning
confidence: 99%
“…In previous studies, we examined the swimming properties of a spiral-type magnetic micro-machine as shown in Fig. 1 [I]- [3]. This micro-machine was composed of a bulk magnet and wire.…”
Section: Introductionmentioning
confidence: 99%